Melatonin receptors, heterodimerization, signal transduction and binding sites: what's new? - Ralf Jockers; Pascal Maurice; Jean A. Boutin; Philippe Delagrange (2008)
Melatonin is a neurohormone that has been claimed to be involved in a wide range of physiological functions. Nevertheless, for most of its effects, the mechanism of action is not really known. In mammals, two melatonin receptors, MT1 and MT2, have been cloned. They belong to the G-protein-coupled receptor (GPCR) superfamily. They share some specific short amino-acid sequences, which suggest that they represent a specific subfamily. Another receptor from the same subfamily, the melatonin-related receptor has been cloned in different species including humans. This orphan receptor also named GPR50 does not bind melatonin and its endogenous ligand is still unknown. Nevertheless, this receptor has been shown to behave as an antagonist of the MT1 receptor, which opens new pharmacological perspectives for GPR50 despite the lack of endogenous or synthetic ligands. Moreover, MT1 and MT2 interact together through the formation of heterodimers at least in cells transfected with the cDNA of these two receptors. Lastly, signalling complexes associated with MT1 and MT2 receptors are starting to be deciphered. A third melatonin-binding site has been purified and characterized as the enzyme quinone reductase 2 (QR2). Inhibition of QR2 by melatonin may explain melatonin's protective effect that has been reported in different animal models and that is generally associated with its well-documented antioxidant properties.